Social Networking Sites As Emerging Communication Avenue For Social Influence Via E-Formity: Insights And Future Perspective In Indian Economy - Kaushal, Dr. Arun (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In rapid changing technological environment, a number of communication tactics are available for marketers of the 21st century that involves several new features including mouth- to- mouth promotion that has taken radical step in the form of social media marketing especially via social networking sites (Ceil, 2019).This new form of marketing is also known as Electronic Word –of- mouth communication (e -WOM) and viral marketing (Roy, Datta, & Mukherjee, 2019). In current paper, an attempt has been made to discuss the hidden insights about significant contributions of social networking sites for social influence in the form of e-formity. In order to proceed for this study, the deep and critical literature review was done by reading the research papers from Jstor, Emerald, Wiley, Taylor and Francis, Science Direct, Elsevier, Google scholar, etc. The information about internet user behavior of top ranked counties will also provide insights and knowledge to researchers or marketing professionals so that online marketing strategies can be cultivated for business organizations accordingly.